Factors that affect the transfer of embryos from alpacas (Vicugna pacos) to llamas (Lama glama) - Perez G., Uri (2020)
The aim of this study was to evaluate the factors that affect the transfer of embryos obtained through simple ovulation in alpacas and transferred to alpacas and llamas. The study was conducted under conditions of the Peruvian Highlands during the reproductive season (December to March). Thirteen donor alpacas (Huacaya = 6, Suri = 7) and 80 recipients (40 alpacas and 40 llamas) with at least 15 postpartum days were selected. The embryo recovery rate in 93 consecutive washes were 88.68% in Huacaya alpacas and 80% in Suri alpacas, and the pregnancy rates were 67.57 and 66.67% in alpacas and llamas, respectively without significant differences in both cases. The variables size and quality of the embryo, location and area of the corpus luteum (CL) in the recipient, species of the recipient (llama, alpaca), donor breed (Huacaya, Suri), body condition score (BCS) of the receptor, depth of the place of deposition of the embryo (total, partial), and uterine horn of deposition of the embryo (right, left) were evaluated. The logistic regression indicated that the factors related to better success of pregnancy were the quality of the embryo (grade 1 and 2), the breed of the donor (Huacaya) and BCS of the recipient (grade 2 and 3).